Spatio‐temporal distribution of sexual calling behaviour in domesticated, sterile and wild Queensland fruit fly males under field cage conditions. Issue 5 (2nd February 2021) - Inskeep, Jess R; Taylor, Phillip W; Mainali, Bishwo; Rempoulakis, Polychronis; Weldon, Christopher W
Abstract: BACKGROUND: The sterile insect technique (SIT) is used in Australia to contain and eradicate outbreaks of Bactrocera tryoni (Froggatt) (Diptera: Tephritidae) in fruit‐fly‐free regions, and to manage populations in some endemic regions. To assess the likely impact of SIT on wild B. tryoni populations it is important to assess the colocation and synchrony of male calling between sterile and wild flies. We observed the location and timing of calling behaviours of marked mass‐reared (fertile and sterile) and wild B. tryoni males in walk‐in field cages. RESULTS: We found that wild males called further from the canopy centre than mass‐reared (fertile or sterile) males. Mass‐reared (fertile or sterile) males called earlier in the evening than wild males and, consequently, mass‐reared males called when temperature and light intensity were higher than when wild males called. CONCLUSION: Male calling is a prerequisite to mating among dacine fruit flies. Therefore, our observations of spatio‐temporal divergence in male calling behaviour may lead to assortative mating between mass‐reared and wild B. tryoni in SIT applications. The importance of these spatio‐temporal differences warrants further inquiry, with particular focus on how environmental conditions modify calling behaviour and avenues to ameliorate differences between sterile and wild flies. © 2021 Society of Chemical Industry Abstract : Domestication leads to temporal and spatial divergence of B. tryoni male calling behaviour in tree canopies, which may limit the effectiveness of SIT programmes.